Modelling entrepreneurship in small-scale enterprises - Salim, Ruhul (Routledge - Taylor and Francis Ltd, 2005)
In the small-scale enterprises, the entrepreneurs and managers are often one and the same. This paper attempts to estimate the entrepreneurial competence in small-scale enterprises decomposing into entrepreneurial ability and managerial efficiency using the frontier production function. The empirical results show that most of the sample enterprises fail to realize their full entrepreneurial potential. The important implication of these results is that small enterprises should generate a different set of rules than large enterprises in the decision-making process that best conduces them to move toward their potential frontier.